2015
DOI: 10.1080/02705060.2015.1050467
|View full text |Cite
|
Sign up to set email alerts
|

Elevational distribution and species diversity of freshwater Ostracoda (Crustacea) in Çankırı region (Turkey)

Abstract: We investigated how the richness and ecological characteristics of non-marine ostracod species varied across nine 100-m elevation bands (from 549 to 1457 m) in theÇankırı region. We collected a total of 37 taxa (25 living and 12 sub-recent) from 114 of 130 aquatic sites sampled during September of 2011; 34 of the taxa were new records for the region. Eight widely distributed 'cosmopolitan' species (Candona neglecta, Cypridopsis vidua, Heterocypris incongruens, Ilyocypris bradyi, Limnocythere inopinata, Potamoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
(29 reference statements)
4
12
0
Order By: Relevance
“…Also, swimming or non swimming species were reported from all of the elevational ranges in the current study. A similar result was reported by Külköylüoğlu et al (2016). The above information enforce the active distribution of ostracods occur in the same habitat but passive distributions happens over geographical ranges.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also, swimming or non swimming species were reported from all of the elevational ranges in the current study. A similar result was reported by Külköylüoğlu et al (2016). The above information enforce the active distribution of ostracods occur in the same habitat but passive distributions happens over geographical ranges.…”
Section: Discussionsupporting
confidence: 89%
“…Canonical Correspondence Analysis results herein (Fig. 2) partially support the findings of Külköylüoğlu et al (2012b), Yavuzatmaca et al (2015), Külköylüoğlu et al (2016) and Külköylüoğlu et al (2017a). In these previous studies, water temperature (Tw), electrical conductivity (EC), pH, elevation (Elev.)…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously stated (e.g., KÜlkÖylÜoğlu et al 2012c, Yavuzatmaca et al 2017a, the high species diversity was reported in the mid-elevational interval in the present study (Table 2). Whereas the finding of high diversity at low (e.g., Pèrez et al 2015 and high (e.g., KÜlkÖylÜoğlu et al 2012aKÜlkÖylÜoğlu et al , 2016 elevational intervals are also available in the literature. The difference between the present study and previous ones is the difference in the elevation ranges used.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the average number of species per sampling site is higher in these regions than many others with similar species composition. For example, Külköylüoğlu et al (2016) recently reported 25 species from 114 sites in Çankırı (Turkey), wherein the number of species per site (0.219) was the lowest among those listed in Table 3. In contrast, there were 18 species found from 42 sites in Zonguldak where the number of species per site was about two times (0.429) greater than in Çankırı.…”
Section: Discussionmentioning
confidence: 99%